Fighting youth unemployment: The effects of active labor market policies - Marco Caliendo; Steffen Künn; Ricarda Schmidl (Institute for the Study of Labor (IZA), 2011)
A substantial number of young unemployed participate in active labor market programs (ALMP) in Germany each year. While the aims of these programs are clear - a fast re-integration into employment or enrollment in further education - a comprehensive analysis of their effectiveness has yet to be conducted. We fill this gap using administrative data on youth unemployment entries in 2002 and analyze the short- and long-term impacts for a variety of different programs. With informative data at hand we apply inverse probability weighting, thereby accounting for a dynamic treatment assignment and cyclical availability of programs. Our results indicate positive long-term employment effects for nearly all measures aimed at labor market integration. Measures aimed at integrating youths in apprenticeships are effective in terms of education participation, but fail to show any impact on employment outcomes until the end of our observation period. Public sector job creation is found to be harmful for the medium-term employment prospects and ineffective in the long-run. Our analysis further indicates that the targeting of German ALMP systematically ignores low-educated youths as neediest of labor market groups. While no employment program shows a positive impact on further education participation for any subgroup, the employment impact of participation is often significantly lower for low-educated youths.
urn:nbn:de:101:1-201201113979
Keywords: J64; J68; J13; 330; youth unemployment; active labor market policy; program evaluation; propensity score weighting; Jugendarbeitslosigkeit; Arbeitsmarktpolitik; Wirkungsanalyse; Deutschland